Altered brain glymphatic function on diffusion-tensor MRI in patients with spontaneous intracerebral hemorrhage: an exploratory study - Xia, Xiaona; Ren, Qingguo; Zhang, Juntao; Guan, Shuai; Jiang, Qingjun; Wei, Ying; Hua, Rui; Zhao, Shen; Hu, Xiangjun; Shi, Feng; Meng, Xiangshui (Frontiers in Aging Neuroscience, 2024)
ObjectivesTo investigate the function of the glymphatic system (GS) and its association with neuropsychological tests in spontaneous intracerebral hemorrhage (sICH) by diffusion tensor imaging analysis along the perivascular space (DTI-ALPS).MethodsThis retrospective study included 58 patients with sICH and 63 age- and sex-matched healthy controls (HCs). Partial correlation analyses were performed to examine the relationships between the DTI-ALPS index and radiological as well as clinical data. Mediation analyses were performed to explore the mediating role of the grey matter proportion (GM%) in the relationship between DTI-ALPS index and Montreal Cognitive Assessment (MoCA) score.ResultsSignificantly lower DTI-ALPS index values were observed in sICH compared with HCs (FDR-p < 0.001). In the acute-subacute sICH group, the ALPS index was significantly correlated with hematoma volume (r = −0.572, FDR-p = 0.031). In the chronic sICH group, the ALPS index was significantly correlated with MoCA scores (r = 0.425, FDR-p = 0.014). In chronic sICH groups, GM% served as a significant mediator in the relationship between the DTI-ALPS index and MoCA scores (indirect effects β = 4.925, 95%CI: 0.028, 11.841). The ALPS index was identified as an independent prognostic indicator for unfavorable outcomes in sICH (β = −9.851, p = 0.018).ConclusionOur study demonstrated that the DTI-ALPS index decreased in sICH patients, suggesting potential functional impairment of the lymphoid system. Additionally, the DTI-ALPS index served as an independent predictor of poor 90-day prognosis. In the acute-subacute stage of sICH, the DTI-ALPS index had negative correlation with hematoma volume. In the chronic sICH group, the GM% partially mediated the relationship between the GS and cognitive function.